A View at the Historical and Ancient Monuments of Kunduz Province-Afghanistan - Wafa, Amanuddin; Sarwari, Atiqullah; Habibi, Habib Rahman (Randwick International of Social Science Journal, 2024)
Kohandej is a combination of two words, alt and dej, meaning fence and old castle. Both words denote a high enclosure, and the historical course of Kunduz, which is the main basis of the enclosure at the time of the Aryan rulers of Balkh, namely Ki Khosro and Qiqbad, was formed in their time 1900 years before Christ. It was conquered and destroyed and rebuilt several times over time, earning it the name Kohandezh. The province of Kunduz, known as Kunduz, Kunduz, "Waki Dej" The kings of this period were also known as Kayanis, which the epic poet Ferdowsi mentions in his book Shahnameh about these kings. Our ancient and historical land of Afghanistan was a place where cultures and trade goods intersected on a regional level, and it has long been considered a trading center between East and West. The Kushans, who founded a large empire in Ariana in the early centuries of the Christian era, traded with neighboring rulers via the Silk Road. Qunduz or Kunduz, originally known as Kohan Dej, is located in northeastern Afghanistan, and its center is the city of Kunduz. This city was the capital of Yaptlian for 110 years. Unfortunately, the historical and ancient areas of Kunduz province have been severely damaged by the internal wars of the last four decades, and no attention has been paid to the insecurities and developments of the last decade. It originates from Islam, Hivan Tseng mentioned the city of Kunduz under the name (Heweh) and regarded it as the center of Buddhism.